(3GdaNQis - (3CHh aNQ GdOjf eMeO Hf GdMSf, GdMGSH GdcQNjs
(3ChdgG (B:s
(3bGd CHh HcQ eMeO Hf GdMSf GdcQei Efi hLOJ GdMSGH ehVhYGJ dENQGL GdeLghdGJ ef GdeYdheGJ ai LejY CfhGYg s
(3BNQgG (B:s
(3eJi jNQL GdecYH hbSeJg Ydi gPG GdhLg jJe cJGH GdaNQi GdeTJed Ydi CUhd GdLHQ hGdebGHdI hCUhd GdeSGFd s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs